Dilemma and global financial cycle: Evidence from capital account liberalisation episodes - Xiang Li (Halle Institute for Economic Research (IWH), 2021)
By focusing on the episodes of substantial capital account liberalisation and adopting a new methodology, this paper provides new evidence on the dilemma and global financial cycle theory. I first identify the capital account liberalisation episodes for 95 countries from 1970 to 2016, and then employ an augmented inverse propensity score weighted (AIPW) estimator to calculate the average treatment effect (ATE) of opening capital account on the interest rate comovements with the core country. Results show that opening capital account causes a country to lose its monetary policy independence, and a floating exchange rate regime cannot shield this effect. Moreover, the impact is stronger when liberalising outward and banking flows.
Keywords: E52; F32; F33; F42; 330; average treatment effect; capital control; global financial cycle; monetary policy autonomy; propensity score matching; trilemma